2001
DOI: 10.1093/toxsci/60.2.296
|View full text |Cite
|
Sign up to set email alerts
|

Defining the Impact of Weakly Estrogenic Chemicals on the Action of Steroidal Estrogens

Abstract: We tested whether bisphenol A (BPA) or o,p'-DDT, when combined with 17beta-estradiol (E2), would contribute to the overall mixture effect using a yeast reporter gene assay, the yeast estrogen screen. Following comprehensive concentration-response analyses of the single agents, the pharmacologically well-founded models of concentration addition and independent action were used to predict entire concentration-response relationships for mixtures of the agents with a variety of fixed mixture ratios, assuming addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 21 publications
3
61
0
4
Order By: Relevance
“…For the quantification of responses, however, one should be extra cautious for the presence of partial and/or superagonistic estrogens. This study confirms the suitability of CA to describe the effects of mixtures of similar acting xeno-estrogens in reporter gene assays as reported earlier (3,12,17,18).…”
Section: Resultssupporting
confidence: 90%
“…For the quantification of responses, however, one should be extra cautious for the presence of partial and/or superagonistic estrogens. This study confirms the suitability of CA to describe the effects of mixtures of similar acting xeno-estrogens in reporter gene assays as reported earlier (3,12,17,18).…”
Section: Resultssupporting
confidence: 90%
“…In a recent study of mixtures of estradiol and the weak xenoestrogens bisphenol A and o,p´-DDT (Rajapakse et al 2001), we found that both the hormone and the xenoestrogens contributed in equal measure to the observed combination effects when combined at concentrations that produced similar responses. Furthermore, model calculations carried out by our group suggested that combinations of a large number of xenoestrogens might modulate the effects of 17β-estradiol, even when each individual xenoestrogen is present at concentrations that alone would not produce measurable effects (Kortenkamp and Altenburger 1999).…”
mentioning
confidence: 77%
“…We followed a protocol developed by Routledge and Sumpter (1996) exactly as described by Rajapakse et al (2001). We obtained singleagent data from at least three experiments run in duplicate, and mixture samples were run in duplicate on at least two separate occasions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Essa avaliação pode depender de alguns fatores, tais como, potência dos componentes da mistura, a relação resposta-concentração (razão de mistura) de uma substância em uma mistura, como também de efeitos como sinergismo e antagonismo que podem desviar os efeitos esperados (Rajapakse et al, 2001;Silva et al, 2002;Jonsson & Aoyama, 2007 (Bautitz, 2010;Borrely, 2001;Haag & Yao, 1992;Buxton et al, 1988).…”
Section: Efeitos De Misturasunclassified